Phenotypic correlations between architectural characteristics and grain yield in dry beans as affected by plant density and locations - Nienhuis, James; Singh, S.P. (1983)
Studies were conducted at CIAT to measure the phenotypic correlations between several architectural characteristics and yield of dry beans as affected by plant density and environment (location). Four bean cv. were used to represent each bush bean growth habit (I, II, III). All 12 cv. were grown at Quilichao and Popayan, and during 2 seasons at Palmira, Colombia; plant densities were 5.0, 13.3, 21.6, and 30.0 plants/m2. Results indicate that architectural characteristics fall into 3 classes with respect to their relationship to yield: (a) traits that are correlated in all environments; (b) traits that are correlated only in specific environments; (c) traits that are not correlated in any environment. The relative importance of the relationship between some architectural traits and yield is to some extent growth habit- specific. (CIAT)